2016
DOI: 10.1136/jfprhc-2015-101190
|View full text |Cite
|
Sign up to set email alerts
|

Assessing women's satisfaction with family planning services in Mozambique

Abstract: Background The contraceptive prevalence rate in Mozambique was estimated as 11.3% in the last Demographic and Health Survey. The impact of family planning (FP) on women's health and on the reduction of maternal mortality is well known. Methods Acknowledging the importance of user satisfaction in the utilisation of health services, exit interviews were used to assess women's satisfaction with FP services in Mozambique. The survey, conducted in 174 health facilities, was representative at the national level, cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 22 publications
8
25
1
Order By: Relevance
“…This is in line with the study among women in Kumasi, Ghana [26] and Mozambique [27]. About one in ten women complained about irregular menses compared to one in five among women in Kumasi, Ghana [26].…”
Section: Discussionsupporting
confidence: 90%
“…This is in line with the study among women in Kumasi, Ghana [26] and Mozambique [27]. About one in ten women complained about irregular menses compared to one in five among women in Kumasi, Ghana [26].…”
Section: Discussionsupporting
confidence: 90%
“…Similar results have been reported by Chavane et al, [6] who studied women's satisfaction with family planning services in Mozambique, they reported that the women are completely satisfied with the family planning services provided to them at different health care facilities.…”
Section: Discussionsupporting
confidence: 77%
“…One of the important factors that influence the use of family planning & other reproductive health services is client satisfaction with health care services [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations